THE EFFECT OF PROFITABILITY, LEVERAGE, WINNER/LOSER STOCKS, AND PUBLIC OWNERSHIP ON INCOME SMOOTHING IN IDX FOOD AND BEVERAGE FIRMS 2023 - Yolanda Danisa; Nor Norisanti; Faizal Mulia Z (Proceeding of International Seminar on Agricultural Conservation and Cultural Heritage, 2025)
The food and beverage subsector showed a significant contribution to Indonesia’s Gross Domestic Product (GDP) from 2020 to 2023, with consistent increases in profit and sales. However, this condition was accompanied by rising debt and declining stock returns, which were not aligned with the positive financial performance, raising suspicions of income smoothing practices as a form of earnings manipulation by management to maintain the company’s image in the eyes of investors. This study aims to examine the effect of profitability, leverage, winner/loser stock, and public ownership on income smoothing. The population of this study includes food and beverage subsector companies listed on the Indonesia Stock Exchange (IDX) in 2023, totaling 95 companies. The sampling technique used was purposive sampling, resulting in 56 companies as the sample. Data analysis was conducted using logistic regression through the SPSS 26. The results of the study show that simultaneously, the variables of profitability, leverage, winner/loser stock, and public ownership influence income smoothing. Partially, leverage variable has a significant effect and shows a positive direction toward income smoothing, winner/lose stock variable has a significant effect and shows a negative direction toward income smoothing, while profitability and public ownership have no significant effect.